2010
DOI: 10.1111/j.1439-0434.2009.01566.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Phytoplasmas Related to ‘Candidatus Phytoplasma asteris’ and Peanut WB Group Associated With Sweet Cherry Diseases in Iran

Abstract: Symptoms suggestive of phytoplasma diseases were observed in infected sweet cherry trees growing in the central regions of Iran. Phytoplasmas were detected in symptomatic trees by the nested polymerase chain reaction (nested PCR) using phytoplasma universal primer pairs (P1⁄Tint, PA2F⁄R, R16F2⁄R2 and NPA2F⁄R). Restriction fragment length polymorphism analyses of 485 bp DNA fragments amplified in nested PCR revealed that different phytoplamas were associated with infected trees. Sequence analyses of phytoplasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…; Zirak et al. ,b, ,b), it was expected that other fruit orchards in these regions might be affected with similar phytoplasmas. For many years, apple tress displaying several symptoms of phytoplasma diseases were observed in orchards located in Isfahan and ChaharMahal‐O‐Bakhtiari provinces.…”
Section: Discussionmentioning
confidence: 95%
“…; Zirak et al. ,b, ,b), it was expected that other fruit orchards in these regions might be affected with similar phytoplasmas. For many years, apple tress displaying several symptoms of phytoplasma diseases were observed in orchards located in Isfahan and ChaharMahal‐O‐Bakhtiari provinces.…”
Section: Discussionmentioning
confidence: 95%
“…In recent years, phytoplasmas of the peanut WB and stolbur groups have been identified as causal agents of many annual crops and trees diseases in Iran (Salehi et al 2005, Zirak et al 2009a, 2009b, 2010a, 2010b. The wide host range of phytoplasmas belonging to the 16SrII and 16SrXII groups is certainly related to the presence of insect vectors.…”
Section: Discussionmentioning
confidence: 99%
“…However, few perennials have been reported that can be affected by 'Ca. Phytoplasma asteris' in Iran (Zirak et al 2009;Hashemi-Tameh et al 2014a, b). It was expected that 'Ca.…”
Section: Resultsmentioning
confidence: 99%
“…In the RFLP analyses, Iranian cherry phytoplasma PCh8 (accession number: FJ204397), which was previously collected from central Iran (Zirak et al 2009), and one almond phytoplasma isolate related to 16SrIX phytoplasma group (isolate P25) which was collected in an area near the investigated regions were used as the reference strains for 'Ca. Phytoplasma asteris' and pigeon pea witches'--broom group respectively.…”
Section: Methodsmentioning
confidence: 99%